Activity-based management for financial institutions : driving bottom line results - Bahnub, Brent (Wiley & SAS business series, 2010)
Discover how to use activity-based management to improve your bottom line The first book of its kind to focus on activity-based management in the financial services industry, Activity-Based Management for Financial Institutions: Driving Bottom Line Results will show you how to drive changes to your organization's bottom line